Extended Investigation of Exposure to Respirable Synthetic Amorphous Silica Dust and Its Potential Impact on Non-malignant Respiratory Morbidity - Yong, Mei; Morfeld, Peter; McCunney, Robert (Frontiers in Public Health, 2022)
Objectives The present analysis aims to study the health impact of an occupational exposure to respirable synthetic amorphous silica (SAS) dusts, based on the available data from the German study. Methods The effect of cumulative exposure to respirable SAS dust on respiratory morbidity were investigated in 462 exposed male workers. Multiple exposure assessments was performed anchored by a most recent measurement series. Internal regression models in addition to Monte Carlo-Multi Model were fitted. Results An averaged cumulative respirable SAS dust concentration of 6.44 mg/m3-years was estimated. Internal regression models suggested a reduction of 8.11 ml (95% confidence interval: 0.49–15.73) in forced vital capacity (FVC) per 1 mg/m3-year increase of exposure. But no effect on forced expiratory volume in 1 s (FEV1) and the ratio of the parameters FEV1/FVC was observed in association with exposure to a respirable fraction of SAS. No adverse effects on the occurrence of respiratory diseases were indicated. Conclusion This study provides no clear evidence of adverse health effects from occupational exposure to respirable SAS. Sponsor Evonik Operations GmbH/Smart Materials, Cabot Corporation, Wacker Chemie AG.